2011
DOI: 10.1016/j.poetic.2011.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The spatial and social contexts of television-viewing adolescents

Abstract: This paper studies television-viewing adolescents within their spatial and social context, using the Uses and Gratifications approach as a typology of uses. Because previous research suggested the importance of gender-based differences in both the frequency of watching TV and of content preferences, but lacked an examination of the social-and spatial-viewing contexts for boys and girls, respectively, a specific emphasis is placed on gender. Results were obtained by means of both quantitative and qualitative me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…In particular, the lack of such media variety in adolescents' personal spaces indicates that the use of some media (i.e. the television set) was still linked to family consumption, as pointed out by previous studies (Adriaens et al 2011;Holloway and Green 2008;Kortii 2011). Despite this, especially in the qualitative phase, we found that they often did not need a television set in their bedroom because they could use the main one almost at any time, or they could access media contents through the computer and the Internet, for instance YouTube videos.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In particular, the lack of such media variety in adolescents' personal spaces indicates that the use of some media (i.e. the television set) was still linked to family consumption, as pointed out by previous studies (Adriaens et al 2011;Holloway and Green 2008;Kortii 2011). Despite this, especially in the qualitative phase, we found that they often did not need a television set in their bedroom because they could use the main one almost at any time, or they could access media contents through the computer and the Internet, for instance YouTube videos.…”
Section: Discussionmentioning
confidence: 77%
“…Besides, even if other home spaces are increasingly dedicated to different forms of screen consumption, and 'despite the availability of multiple television sets, the main television set still has great appeal to everyone in the house as the "first choice" television', precisely because it is the largest or the latest model and is usually positioned in the most comfortable position (Holloway and Green 2008: 50). Moreover, watching television in the living room often offers teenagers the opportunity to share social interaction and television-centred communication with the rest of the family (Adriaens et al 2011).…”
Section: Young People's Media Usage and Leisure Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Discussions lasted between 60 and 75 minutes, after which participants were given their incentive for contributing. One can criticise the artificial nature of watching and discussing media content in groups, but previous research (Ging 2005, Adriaens et al 2011b) has shown that film and television are often discussed among friends and peers. Moreover, 'TV talk is a crucial forum for experimentation with identities' (Gillespie 1995, p. 25).…”
Section: Methodsmentioning
confidence: 99%
“…Las diferencias de género se reflejan, también, en las pautas de consumo mediático (Adriaens, Van-Damme & Courtois, 2011;Alcolea, 2014) de chicos y chicas, respectivamente. Se trata, pues, de patrones de consumo opuestos y diferenciados entre sí.…”
Section: El Smartphone Redes Sociales Y Consumo Multipantallaunclassified